Synonymy and Antonymy of Ukrainian Meteorological Terms - Заверющенко, Ольга Леонідівна; Заверющенко, Микола Петрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article analyses the system relations, in particular synonymy and antonymy, in Ukrainian meteorological terminology basing on the materials of the Russian-Ukrainian meteorological dictionary and textbooks on meteorology and related sciences. Special attention is paid to synonymy in general language and terminology. Types of synonyms of Ukrainian meteorological industry are determined on the bases of term synonyms classification: lexical and syntactic synonyms are singled out as well as analytical term units with synonymic components. According to another classification, pairs of meteorological terms that are full synonyms are singled out. Among the synonyms of meteorological sphere, cognate paronyms are given as a separate group. Thematic groups of synonymous term units of meteorological sphere are named.The semantic structure of antonymous terms is commented on, the possibility of general language oppositions or terminological oppositions is accentuated as feature of term antonyms. Contradictory, contrary, complementary and conversion antonyms are singled out in meteorological terminology. Meteorological term antonyms are divided into lexical and derivative ones, their origin is determined as well as part-of-speech and thematic group. The scarce antonyms of the meteorological industry that are opposed to parts of compound words are given. The correlation of etymologically Ukrainian and borrowed meteorological terms and term elements with opposite meaning is established. The models of analytical (two-, three- and multicomponent) meteorological terms that enter into antonymous relations are described. The filling of such models and the theme groups of the opposed components of analytical meteorological combinations are looked into.